:Estúdio, Ano 1, nº1 (2010) - Queiroz, João (2021)
Contém os seguintes capítulos: 1. Recriar, p.18. - 2. Consonâncias, p.54. - 3. Restaurador, p.96. - 4. Olhares, p.142. - 5. Apropriações, p.190. - 6. Realidades, p.234. - 7. Singularidade, p.274. - 8. Usar, p.320